A follow‐up questionnaire survey 2022 on radiation protection among 464 medical staff from 34 endoscopy–fluoroscopy departments in Japan. Issue 1 (13th April 2023) - Hayashi, Shiro; Takenaka, Mamoru; Kogure, Hirofumi; Yakushijin, Takayuki; Nakai, Yousuke; Ikezawa, Kenji; Yamaguchi, Shinjiro; Fujisawa, Toshio; Tamaru, Yuzuru; Maetani, Iruru; Maruyama, Hirotsugu; Asai, Satoshi; et al.
Abstract: Objectives: We surveyed and reported low protective equipment usage and insufficient knowledge among endoscopy‐fluoroscopy departments in Japan in 2020. Two years later, we conducted a follow‐up survey of doctors, nurses, and technologists in Japan. Methods: We conducted a questionnaire survey on radiation protection from May to June 2022. The participants were medical staff, including doctors, nurses, and radiological and endoscopy technicians in endoscopy‐fluoroscopy departments. The questionnaire included 17 multiple‐choice questions divided into three parts: background, equipment, and knowledge. Results: We surveyed 464 subjects from 34 institutions. There were 267 doctors (58%), 153 nurses (33%), and 44 technologists (9%). The rate of wearing a lead apron was 98% in this study. The rates of wearing a thyroid collar, lead glasses, and radiation dosimeter were 27%, 35%, and 74%, respectively. The trend of the protective equipment rate was similar to that of our previous study; however, radiation dosimetry among doctors was still low at 58%. The percentage of subjects who knew the radiation exposure (REX) dose of each procedure was low at 18%. Seventy‐six percent of the subjects attended lectures on radiation protection, and 73% knew about the three principles of radiation protection; however, the concept of diagnostic reference levels was not well known (18%). Approximately 60% of the subjects knew about the exposure dose increasing cancer mortality (63%) and the 5‐year lens REX limit (56%). Conclusions: There was some improvement in radiation protection equipment or education, but relatively little compared to the 2020 survey of endoscopy departments.